The role of the middle class in achieving social integration - الملقي دانية (Latakia University Journal - Economic and Legal Sciences Series, 2024)
The middle class is the mainstay of the social structure within the state because it includes the largest number of the state’s population, as well as the type because it includes different segments of citizens with different specializations, ages, and orientations. Because of its importance, the middle class was the true safety valve of the state against any external aggression or attempt to destabilize internally. Unfortunately, recently, due to economic and political changes, we have noticed a decline in the number of the middle class, as well as a defect in the social structure, which has truly caused a state of instability within the country. These variables led to a state of instability that spread and affected the middle class and affected its actual presence within society. The middle class is the class that maintains or overpowers, destroys or builds, kindles or extinguishes. The survival of the middle class, the effectiveness of its role and the extent of its influence in society, is evidence of the success of the state’s political and economic plans. Its disappearance is evidence of a failure to do so. The middle class works to achieve social integration within the state and the unity of its ranks, because it is not from the upper class that has made power or money forget the needs and requirements of the people, and it is not from the lower class that does not know how to express its needs, does not realize the true meaning and purpose behind every political decision or action, and does not give importance to the process. Political participation. The middle class is the mainstay of the unity of society and the achievement of social integration within it. Therefore, the factors and reasons for its decline must be studied, as well as the importance and centrality of its role explained, and work must be done to enhance its presence and survival through reform plans.